PERFORMANCE ASSESSMENT ANALYSIS OF RSIA UMMU HANI USING A BALANCED SCORECARD APPROACH - Tri Retno Wasis; Siti Maghfiroh (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
This study aims to determine the hospital’s performance assessment with the Balanced Scorecard approach. The object of this research is a private hospital in Purbalingga. The research method used is a case study quantitative research method. This study’s data collection techniques used financial statement documentation for secondary data. The results showed that the hospital’s performance assessment from the three balanced scorecard perspectives was quite good. It was concluded that: (1) the financial perspective is good in terms of financial ratios following the criteria; (2) the customer perspective is quite good based on the result of the calculation of customer retention and customer acquisition; (3) the internal business perspective is quite good based on the result of the percentage of BOR, TOI, LOS, and BTO values is not following the Minister of Health standards No. 1171 of 2011; and (4) the perspective of growth and learning is quite good because based on HR training data regarding employee retention and employee training.